The Effect of Goat Grazing on the Biodiversity of Pannonian Dry Grassland - Karoly Penksza; Ferenc Pajor; Andrea Kevi; Zsombor Wagenhoffer; Laszló Sipos; Eszter Salata-Falusi; Peter Penksza; Peter Poti; Jozsef Berke; Denes Salata; Marta Bajnok; Szilard Szentes (Diversity)
In this study, we analyzed the phytosociological data from four sample sites located in the Pannonian region. The study areas, ranging from 2.4 to 2.5 hectares, have been subjected to goat grazing and mowing for 24 years. N1: Nagyréde, an overgrazed pasture with 24 goats; N2: Nagyréde, a mown field; C1: Csokvaomány, a lightly grazed pasture with 12 goats; and meadow C2: Csokvaomány, a site that is both mown and grazed. Six phytosociological surveys were conducted randomly in each area. We also considered the conservation value, biomass production, and forage values. Phytosociological data were processed using hierarchical cluster analysis and the non-parametric Kruskal–Wallis test. The overgrazed pasture (N1) exhibited the most degraded vegetation community, dominated by weeds and disturbance-tolerant species. The overgrazed (N1) pasture had a low forage value because of the different timing of treatments. Even in the lightly grazed pasture (C1), the proportion of species indicative of degradation was significant. The species composition of the areas indicated that the mown and subsequently grazed area (C2) had outstanding values. The species richness of C2 was twice that of the mown field (N2). Based on the present study, a combination of light grazing pressure and mowing is the most suitable approach for managing and economically utilizing these grasslands.